Getting stoned with savages : a trip through the Islands of Fiji and Vanuatu - Troost, J. Maarten (Broadway Books, 2006)
Describes travel experiences in Vanuatu and Fiji, which include coping with Mother Nature--typhoons, earthquakes, volcanoes--and observing the relaxed lifestyle of the islanders and their attitudes toward new parenthood.